Makna Agama bagi Remaja di Tengah Perkembangan Media Sosial - Muhammad Fahmi Aliyansyah; Mutiara Dewi Kencanawati; Naila Muthiah; Yuminah Rahmatullah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
The development of social media has a major influence on the lives of Muslim adolescents, especially in shaping their understanding and practice of religion. This study uses a semi-structured in- depth interview method with 10 adolescents aged 15-19 years in Jakarta and surrounding areas to explore the meaning of religion in the context of social media. The results show that religion is seen as a source of peace, moral guidance, and social identity, while social media acts as a means of education as well as a source of challenges in religious practice. This study concludes that critical guidance on the use of social media is needed by families and educators so that adolescents can interpret religion in a healthy way in the digital era.